2021
DOI: 10.1021/acs.joc.1c00452
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Lactamization of (E)-2-(2-Bromophenyl)-3-arylacrylamides for the Synthesis of (E)-3-Arylideneindolin-2-ones

Abstract: A copper-catalyzed, ligand-free intramolecular C−N coupling of (E)-2-(2-bromophenyl)-3-arylacrylamides has been developed. This protocol provides an efficient and practical synthetic route for the biologically important (E)-3-arylideneindolin-2ones from o-bromophenylacetic acids and aromatic or conjugated alkenyl aldehydes. Readily available starting materials, mild and noble metal-free conditions, high efficiency, and good tolerability for phenolic hydroxyl groups make this approach attractive and applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…DBU), the naphtho‐fused oxindole 4 rather than 3‐arylquinolin‐2‐one 2 aq was obtained in 54 % yield, whereas the 3‐arylideneindolin‐2‐one 3 was delivered in 48 % yield under previously reported conditions (procedure B: 20 mol % Cu 2 O, 1.2 equiv. K 2 CO 3 ) [23b] . These results indicated that the 5‐ exo‐trig cyclization would be more advantageous over the 6‐ exo‐trig cyclization of 1 aq at the first stage.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…DBU), the naphtho‐fused oxindole 4 rather than 3‐arylquinolin‐2‐one 2 aq was obtained in 54 % yield, whereas the 3‐arylideneindolin‐2‐one 3 was delivered in 48 % yield under previously reported conditions (procedure B: 20 mol % Cu 2 O, 1.2 equiv. K 2 CO 3 ) [23b] . These results indicated that the 5‐ exo‐trig cyclization would be more advantageous over the 6‐ exo‐trig cyclization of 1 aq at the first stage.…”
Section: Resultsmentioning
confidence: 83%
“…Initially, ( E )‐3‐(2‐bromophenyl)−N‐ethyl‐2‐phenylacrylamide 1 a which was readily obtained via Perkin condensation between 2‐bromophenylaldehyde and phenylacetic acid, [23b,24] followed by condensation with ethylamine, was used as the model substrate for the investigation of reaction conditions (Table 1). To our delight, when the reaction was carried out in the presence of Cu 2 O (20 mol %) and NaOH (0.7 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…A plausible mechanism for the silylative aminocarbonylation protocol was proposed (Scheme 4). 5–12 Oxidative addition of the active Rh I species to silane 2a forms the H–Rh III –Si complex intermediate A. 12 Subsequently, coordination of the Rh III complex intermediate A with the N -(2-ethynylphenyl)acrylamide intermediate B, which is in situ generated from the reaction of 2-alkynylaniline 1 with acryloyl chloride and K 2 CO 3 , affords the intermediate C. Therein, intermediate C containing an acryl transient chelating group can strongly coordinate with the Rh III species, thus resulting in cis -silylrhodation across the CC bond to form the cis -silyl vinyl-Rh III intermediate D. 11,12 Intermediate D may undergo two pathways for the insertion of CO: 5 c – f ,8,12 One is the direct insertion of CO into the vinyl–Rh bond with the simultaneous formation of a N–Rh bond via the reductive loss of the acryl group with the aid of the base (K 2 CO 3 ) 12 j , k to generate the carbonyl-Rh III –N six-membered ring intermediate F; the other involves the formation of the vinyl-Rh III –N five-membered ring intermediate E through the reductive decomposition of the acryl C(sp 2 )–N bond with the aid of the base, 12 j , k followed by the insertion of CO to generate the intermediate F. The reductive elimination of intermediate F results in the desired product ( Z )-4 and regenerates the active Rh I species.…”
Section: Resultsmentioning
confidence: 99%
“…Classical approaches for the assembly of methylene oxindoles mainly involve the intermolecular condensation of oxindoles with aryl carbonyl compounds, including diaryl ketones and aromatic formaldehydes, but these transformations face serious stereoselective control issues and substrate scope limitations. 1,3 To overcome these issues, transition-metal-catalyzed tandem annulation reactions with unsaturated hydrocarbons, 4 such as cross-coupling-enabled annulation cascades of N -(2-haloaryl)propiolamides, 5 N -arylpropiolamides, 6 or 2-(alkynyl)arylisocyanates; 7 the carbonylative annulation of 2-alkynylanilines or 2-alkenylanilines; 8 the chloroacylation of alkyne-tethered carbamoyl chlorides; 9 and the cross-dehydrogenation coupling (CDC) of 2,3-diarylacrylamides or N -cinnamoylanilines, 10 have been developed. Common transition-metal catalysts (such as those containing Pd, Rh, Co 2 Rh 2 , and Ni) are efficient for use in these transformations to access various functionalized 3-methylene-oxindoles; however, the careful control of stereoselectivity sometimes remains a problem, with most configurations being unknown before the conclusion of the reaction.…”
Section: Introductionmentioning
confidence: 99%